Turnover and Price in the Housing Market: Causation, Association or Independence? - Daniel Hallberg; Per Johansson (Uppsala University, Department of Economics, 2002)
We give general conditions for the data generating process to facilitate the testing of structural dependence of turnover on the average (or median) price in the homogenous housing market. Furthermore, the implications of aggregation over sub-markets is studied. A plausible explanation of the disparate empirical findings in this literature may be aggregation over heterogenous sub-markets. This conclusion is supported by empirical findings using longitudinal quarterly data for 289 Swedish municipalities during 1981:1-2000:2.
urn:nbn:se:uu:diva-2232
Keywords: C43; C51; D10; 330; Aggregation bias; House price; Volume of trade; Search; Wohnungsmarkt; Immobilienpreis; Bias; Theorie; Schweden